2017
DOI: 10.4102/hsag.v22i0.961
|View full text |Cite
|
Sign up to set email alerts
|

The motivational needs of primary health care nurses to acquire power as leaders in a mine clinic setting

Abstract: Primary health careLeader Power Survey a b s t r a c t Motivation is a process that influences and directs behaviour in order to satisfy a need. It links with goal 3 of the sustainable development goals that focus on ensuring healthy lives and promoting well-being at all ages. Motivation of nurses is important in the primary health care environment of, for instance, mine settings; since low levels of motivation among Primary Health Care (PHC) nurses could have a negative effect on the achievement of high stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
1
9
1
1
Order By: Relevance
“…The second most predominant motivation is instrumental motivation. Nurses motivated instrumentally believe that behavior should lead to a concrete result, such as reward, promotion, or increased salary . In line with previous studies, one of the most essential motivation sources is reward.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The second most predominant motivation is instrumental motivation. Nurses motivated instrumentally believe that behavior should lead to a concrete result, such as reward, promotion, or increased salary . In line with previous studies, one of the most essential motivation sources is reward.…”
Section: Discussionsupporting
confidence: 66%
“…This study's results show that there is a significant difference in the motivation mean between males and females ( P = 0.034), and this may be because female nurse's social roles, needs, and values are different from those of male nurses . However, this result is inconsistent with findings from research studies conducted by Ayyash and Aljeesh and De Cooman et al Their results showed that there is no significant difference in motivation level between men and women, which is similar to the Jooste and Hamanib () study results . The second considerable finding in the study indicates that there is a significant difference in the motivation mean among nurses with variant years of experience.…”
Section: Discussioncontrasting
confidence: 44%
“…The referral and recall process in our study depended on teamwork and communication within the facility, as healthcare professionals needed to share information with the clerk to ensure that referral and recalls were issued and closed appropriately. Therefore, facility-based variation was influenced by interpersonal relationships within the facility, with these relationships being critical to how well a facility functions [45]. Finding recall or referral outcome information from individual client folders was difficult.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Papathanasiou, Fradelos, Kleisiaris, Tsaras, Kalota, and Kourkouta 2014) "motivation is the process of mobilizing a person's actions in order to fulfill a need or success of a desired target." Health workers, especially nurses need motivation in order to attain quality health care as well as promote meaningful healthy relationships (Jooste & Hamani, 2016). Motivation is very important for every worker to exhibit a behavior that will assist attain the goals and objectives of every organization thus improve the performance over time.…”
Section: Background and Rationale Of The Studymentioning
confidence: 99%